2011
DOI: 10.1111/j.1476-5381.2011.01351.x
|View full text |Cite
|
Sign up to set email alerts
|

Arvelexin from Brassica rapa suppresses NF-κB-regulated pro-inflammatory gene expression by inhibiting activation of IκB kinase

Abstract: BACKGROUND AND PURPOSEBrassica rapa species constitute one of the major sources of food. In the present study, we investigated the anti-inflammatory effects and the underlying molecular mechanism of arvelexin, isolated from B. rapa, on lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages and on a model of septic shock induced by LPS. EXPERIMENTAL APPROACHThe expression of Inducible nitric oxide synthase (iNOS) and COX-2, TNF-a, IL-6 and IL-1b were determined by Western blot and/or RT-PCR respectively. To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 35 publications
4
43
0
Order By: Relevance
“…NF-jB-dependent reporter gene assay and Western blotting revealed that 7-HMIA inhibited the transcriptional activity of NF-jB and the level of p65, subunits of NF-jB, in nuclear fractions. These results are in agreement with our previous finding that arvelexin down-regulated the LPS-induced inflammatory NO and cytokines via inhibition of NF-jB in RAW 264.7 macrophages [19]. Furthermore, Western blotting revealed that 7-HMIA significantly decreased the LPS-induced phosphorylation of Akt.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…NF-jB-dependent reporter gene assay and Western blotting revealed that 7-HMIA inhibited the transcriptional activity of NF-jB and the level of p65, subunits of NF-jB, in nuclear fractions. These results are in agreement with our previous finding that arvelexin down-regulated the LPS-induced inflammatory NO and cytokines via inhibition of NF-jB in RAW 264.7 macrophages [19]. Furthermore, Western blotting revealed that 7-HMIA significantly decreased the LPS-induced phosphorylation of Akt.…”
Section: Discussionsupporting
confidence: 94%
“…Unfortunately, the molecular factors leading mPGES-1 mRNA stabilization are poorly known. Several reports have demonstrated that MAPKs (JNK, p38 kinase, and ERK) signaling regulates inflammatory genes through alterations in transcriptional efficiency [19,32] and also via the mRNA decay system [33][34][35]. The JNK1/2 inhibitor, SP600125, abrogated the increases in mPGES-1 mRNA stability, mPGES-1 protein synthesis, and PGE 2 release induced by IL-1b or LPS in cardiomyocytes [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study also indicated that MAPKs indeed participated in regulating LPS-induced pro-inflammatory mediators, and some natural compounds can possess anti-inflammatory activity by modulating MAPK activation (Kim et al, 2009;Shin et al, 2011). Similarly, fucosterol was found to inhibit the LPS-induced phosphorylations of p38 MAPK and MKK3/6, the latter of which is upstream of p38 MAPK.…”
Section: Discussionmentioning
confidence: 90%
“…In macrophages, the MAPK signaling pathway is one of the most extensively investigated intracellular signaling cascades involved in the LPS-induced inflammatory response (5)(6)(7)(8). The MAPK pathway is comprised of at least three signaling components: Extracellular signal-regulated kinases 1/2 (ERK 1/2); c-Jun N-terminal kinase (JNK); and p38 MAPK, all of which have been demonstrated to induce the release of immune-related cytotoxic factors and proinflammatory cytokines (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%